Teachers' Perceptions about the Implementation of Independent Learning Curriculum in Science Education - Sijabat, Apriani; Juanta, Palma; Gunawan, Revi Gina; Lufri, Lufri; Asrizal, Asrizal; Hardeli, Hardeli (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
This study aims to: Describe teachers' perceptions about the implementation of the independent learning curriculum in science education and describe the constraints felt by teachers in implementing the independent learning curriculum as well as solutions to overcome these obstacles. This type of research is a case study. The sample in this study was a science teacher at SMP DR Wahidin Sudirohusodo Medan, who were selected using a purposive sampling technique and developed using a snowball sampling technique. Data collection was carried out through interviews and questionnaires. Data analysis techniques were carried out in an interactive descriptive manner. The results of this study indicate that the teacher's perception is positive because they welcome the implementation of the independent learning curriculum, supported by adequate socialization and training so that they can apply the concept of learning science in accordance with the independent learning curriculum. Constraints experienced by teachers in the form of technical and non-technical constraints. There are several factors that become obstacles, namely, the first is the inadequate quality of the teacher's human resources, the second is that the facilities and learning resources are minimal or the infrastructure is inadequate and the teacher is clueless, the third teacher is comfortable with the old standard and has no experience in learning independent study.